2015
DOI: 10.2174/1568026615666150114160543
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species, Redox Signaling and Neuroinflammation in Alzheimer's Disease: The NF-κB Connection

Abstract: Oxidative stress and inflammatory response are important elements of Alzheimer's disease (AD) pathogenesis, but the role of redox signaling cascade and its cross-talk with inflammatory mediators have not been elucidated in details in this disorder. The review summarizes the facts about redox-signaling cascade in the cells operating through an array of kinases, phosphatases and transcription factors and their downstream components. The biology of NF-κB and its activation by reactive oxygen species (ROS) and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 137 publications
(267 reference statements)
2
71
0
Order By: Relevance
“…Numerous studies have shown that NF‐κB is an important inflammatory transcriptional regulator that can be activated by oxidative stress . Under normal circumstances, NF‐κB is composed of multiple subunits in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that NF‐κB is an important inflammatory transcriptional regulator that can be activated by oxidative stress . Under normal circumstances, NF‐κB is composed of multiple subunits in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…[34,35] ROS overexpression secondary to oxidative stress can negatively affect proteins, lipids, nucleic acids, carbohydrates, and other molecules and leads to cell membrane lipid peroxidation, protein denaturation, DNA damage, inflammation, cell proliferation, cell dysfunction, and apoptosis. [36] Thus, ROS may play a role in the pathogenesis of several diseases, such as atherosclerosis, [37] cancer, [38] diabetes mellitus, [39] infection, [40] central nervous system disorders, [41] and testicular torsion due to its involvement in lipid peroxidation. [38] In addition, negative effects of oxidative stress on the testes after the initiation of reperfusion have been reported in the testicular torsion induced rat model.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the nature of the subunits binding to the NF-kB binding sites may determine whether up- or downregulation of BACE1 gene takes place 45. Similarly, though NF-kB is a redox-sensitive transcription factor, its interaction with ROS is complex and may lead to either activation and enhanced nuclear translocation in certain experimental conditions or decreased nuclear binding in others 48. However, oxidative stress-induced increased BACE1 activity has been reported in many experimental systems 46,49.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%